LAJU DEKOMPOSISI SERASAH DAUN PADA EKOSISTEM RIPARIAN DI BULUHCINA SEBAGAI RANCANGAN MODUL PEMBELAJARAN BERBASIS PENDEKATAN KONSTRUKTIVISME DAN PETA KONSEP - Anggrahini, Fify; Yustina, Yustina; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to determine the rate of leaf litter decomposition in the riparin ecosystem in Buluhcina and produce a learning module design based on a constructivism approach and concept map. This research was conducted on the riparian ecosystem in Buluhcina and in the Biology Education Laboratory of FKIP Riau University, in May-July 2019. This research was a descriptive study using survey methods. Site selection is done by purposive sampling. Where each research site consists of 3 research plots measuring 20x20 meters. Systematic sampling of litter bags is laid down. Litter bag collection is carried out 4 times every 15 days for 60 days of research. Litter was roasted for 48 hours with a temperature of 80º C. Measurement of environmental factors such as: soil temperature, soil moisture and soil pH was carried out simultaneously with the collection of litter bags. The results showed that the average rate of leaf litter decomposition in the three study sites in the riparian ecosystem in Buluhcina for 60 days of research experienced a rapid decomposition rate that ranged from 0.044 gr/day - 0.102 gr/day. Thus based on the needs of riparian forest ecosystems for organic matter to meet the nutrient supply in Buluhcina has reached the needs needed in maintaining the balance of riparian forest ecosystems in order to be well preserved.Key Words: Litter Decomposition Rate, Riparian Ecosystem in Buluhcina, Module